PCR-RFLP METHOD IN COMBINATION WITH ON-CHIP ELECTROPHORESIS AS A TOOL FOR DETERMINING OF VARIABILITY BETWEEN IMPORTANT SPECIES OF ASPERGILLUS - Ćurčić, Nataša; Ćurčić, Nataša; Miljanić (Krulj), Jelena; Boćarov Stančić, Aleksandra; Vukelić, Igor; bodroža solarov, marija (Food and Feed Research, 2024)
Abstract: Aspergillus species are among the most significant producers of aflatoxins, which can contaminate a wide range of agricultural and food products at any stage of production. The aim of this research was to utilize molecular methods to determine and characterize the variability between isolates of standard Aspergillus species. Genomic DNA was isolated from the mycelium of all tested Aspergillus isolates. PCR amplifications were performed using gene-specific primers. The PCR method successfully amplified the ITS1-5.8S rDNA-ITS2 region and portions of the β-tubulin and calmodulin genes of all tested Aspergillus isolates. PCR products obtained after amplification with primer pairs (ITS1/ITS4 and Bt2a/Bt2b), followed by digestion with restriction enzymes HhaI, MwoI, and AlwI in RFLP analysis, facilitated the identification of variability among the studied Aspergillus species. The results of PCR-RFLP analysis on the tested isolates were consistent with those previously obtained through morphological examinations, indicating the effectiveness of this molecular method for identification and determination of variability among important Aspergillus species. The presented molecular method based on PCR-RFLP analysis, due to its advantages such as reproducibility, speed, and high sensitivity, represents a valuable tool for monitoring and controlling contamination by Aspergillus species in the food supply chain. The method described in this study can be successfully used for rapid identification and determination of variability between isolates of Aspergillus species, contributing to improved food safety control and public health.
Keywords: vrste Aspergillus, β tubulin, restrikcioni enzimi, polimorfizam dužine restrikcionog fragmenta